1998
DOI: 10.1177/10454411980090030601
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Engineering of Skin

Abstract: The skin plays a crucial role in protecting the integrity of the body's internal milieu. The loss of this largest organ is incompatible with sustained life. In reconstructive surgery or burn management, substitution of the skin is often necessary. In addition to traditional approaches such as split-or full-thickness skin grafts, tissue flaps and free-tissue transfers, skin bioengineering in vitro or in vivo has been developing over the past decades. It applies the principles and methods of both engineering and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
4

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(59 citation statements)
references
References 108 publications
1
54
0
4
Order By: Relevance
“…It is noteworthy that oral administration of EBNE increased dermal thickness in ovariectomized rats, because thinning of the dermal layer is associated with skin aging in human subjects. 22) In conclusion, oral administration of EBNE increased bone strength and dermal thickness in ovariectomized rats. We did not find any anti-osteoporosis mechanism of EBNE in this study, and this needs further elucidation.…”
Section: Improvement Of Bone Strength and Dermal Thickness Due To Diementioning
confidence: 81%
“…It is noteworthy that oral administration of EBNE increased dermal thickness in ovariectomized rats, because thinning of the dermal layer is associated with skin aging in human subjects. 22) In conclusion, oral administration of EBNE increased bone strength and dermal thickness in ovariectomized rats. We did not find any anti-osteoporosis mechanism of EBNE in this study, and this needs further elucidation.…”
Section: Improvement Of Bone Strength and Dermal Thickness Due To Diementioning
confidence: 81%
“…A dermal equivalent should be best made out of human, rather than animal, collagen. The human collagen (dermis) helped to promote deposition of additional basement membrane constituents, showed a better pattern of keratinocyte differentiation and had less immunogenicity than the animal collagen [Boyce, 1996;Pomahac et al, 1998]. Lastly, the use of a dermal equivalent enhances the handling characteristics of the equivalent.…”
Section: Introductionmentioning
confidence: 99%
“…The field was largely developed in order to address the shortage of tissues and organs available for transplantation [18]. Previous studies have shown that cells grown on a polymer scaffold were able to reconstruct complex tissues correctly, including bone, skin, cartilage and blood vessels [19][20][21][22][23][24][25]. In the past 20 years, retinal transplantation has been investigated.…”
Section: Polymer Scaffoldsmentioning
confidence: 99%